Epidemiology of injuries in Olympic sports - Lambert, C.; Ritzmann, R.; Akoto, R.; Lambert, M.; Pfeiffer, T.; Wolfarth, B.; Lachmann, D.; Shafizadeh, S. (International Journal of Sports Medicine, 2022)
Injuries effect the performance of athletes. Severity of injuries is determined by time loss and sporting performance reduction. To treat injuries adequately, it is necessary to get an overview of varied injuries types in different sports disciplines. In a retrospective study 7.809 athletes from Germany, Switzerland and Austria competing in competitive or recreational levels of sports were included. Injury prevalence was highest in team sports (75%), followed by combat (64%), racquet (54%) and track and field (51%). Knee (28%) and shoulder (14%) were the most at risk joints. Time loss in sporting activity after injury was longest in the region of knee (26 weeks). Of all reported injuries, 48% were accompanied by a reduced level of performance. The highest injury prevalence occurred in the year 2016 (45%). More injuries occurred during training (58%) compared to competition (42%). Across Olympic disciplines, a large number of injuries occurred during training sessions. Injury frequency increased as the Olympic games drew closer. Knee and shoulder injuries were the most severe injuries with respect to time loss and reduction sporting performance.